Proceso de atención en enfermería en recién nacido con síndrome de abstinencia neonatal. - Lara Prado, Yelena María (2021)
Drugs are chemicals that are released into an individual's body, causing dependence or addiction to the same substances, which can cause clinical symptoms in patients ranging from hallucinations to death. Neonatal abstinence syndrome involves a set of health problems that the baby may experience after the mother is exposed to tobacco, alcohol and drugs. It is revealed to a neonate with pathological history where mother consumed illicit substances during gestation who obtained a single live product was born in the gynecology area where after 2 hours of birth I present loud cry vomiting diarrhea, where he is admitted to the neonatology area vital signs were controlled, he was evaluated by the attending physician who asked for laboratory studies and to obtain the results is diagnosed with neonatal abstinence, prescribed medication is administered, a careful assessment was provided by health personnel applying Marjory Gordon's model of the 11 functional patterns and the NANDA, NOC, NIC taxonomies. The present structuring is carried out through a useful tool that is the Nursing Process, being the assessment the first step in this process and forms the basis of all other processes knowing the state of the hospitalized patient in the area of neonatology using medical records, observation, clinical examinations thus identifying the altered needs to correct the dysfunctional patterns of the neonate through care of the neonat health personnel or are discharged from the hospital.